Anomalies in b→s Transitions and Dark Matter - Avelino Vicente (Advances in High Energy Physics)
Since 2013, the LHCb collaboration has reported on the measurement of several observables associated with b→s transitions, finding various deviations from their predicted values in the Standard Model. These include a set of deviations in branching ratios and angular observables, as well as in the observables RK and RK⁎, specially built to test the possible violation of Lepton Flavor Universality. Even though these tantalizing hints are not conclusive yet, the b→s anomalies have gained considerable attention in the flavor community. Here we review new physics models that address these anomalies and explore their possible connection to the dark matter of the Universe. After discussing some of the ideas introduced in these works and classifying the proposed models, two selected examples are presented in detail in order to illustrate the potential interplay between these two areas of current particle physics.